Case report: Confusing lung signs – is the source of the disease in the lungs or intestines? - Zhao, Xiying; Mo, Jiahao; Zhang, Beiping; Zhang, Haiyan (Frontiers in Medicine, 2023)
At the time of the spread of the COVID-19 epidemic, blurred lung signs suggested by imaging examination are particularly common. Novel coronavirus infection is mainly caused by respiratory symptoms. In the early stage of imaging examination, multiple small patchy shadows or ground glass shadows and invasive shadows of both lungs are dominant. While the pulmonary involvement in Crohn’s disease (CD) is rare and not widely reported. For CD patients, the pulmonary manifestations do not belong to its routine symptoms. The lung involvement of CD patients is difficult to attract clinicians’ attention. If CD patients have vague lung manifestations but have no response to routine treatment, they should consider the respiratory diseases related to CD. We describe a rare case of granulomatous inflammation associated with Crohn’s disease. The patient do not respond to conventional treatment. The final treatment plan was CD immunomodulatory therapy (oral corticosteroids and azathioprine). After treatment, a review of the lung CT showed focal fibrosis and significant improvement in the lung lesions. It suggests that CD related respiratory diseases should be considered when CD patients have abnormal lung manifestations that do not respond to conventional treatment.